Hepatic stellate cells limit hepatocellular carcinoma progression through the orphan receptor endosialin - Carolin Mogler; Courtney König; Matthias Wieland; Anja Runge; Eva Besemfelder; Dorde Komljenovic; Thomas Longerich; Peter Schirmacher; Hellmut G Augustin (EMBO Molecular Medicine, 2017)
Abstract Hepatocellular carcinoma (HCC) is among the most common and deadliest cancers worldwide. A major contributor to HCC progression is the cross talk between tumor cells and the surrounding stroma including activated hepatic stellate cells (HSC). Activation of HSC during liver damage leads to upregulation of the orphan receptor endosialin (CD248), which contributes to regulating the balance of liver regeneration and fibrosis. Based on the established role of endosialin in regulating HSC/hepatocyte cross talk, we hypothesized that HSC‐expressed endosialin might similarly affect cell proliferation during hepatocarcinogenesis. Indeed, the histological analysis of human HCC samples revealed an inverse correlation between tumor cell proliferation and stromal endosialin expression. Correspondingly, global genetic inactivation of endosialin resulted in accelerated tumor growth in an inducible mouse HCC model. A candidate‐based screen of tumor lysates and differential protein arrays of cultured HSC identified several established hepatotropic cytokines, including IGF2, RBP4, DKK1, and CCL5 as being negatively regulated by endosialin. Taken together, the experiments identify endosialin‐expressing HSC as a negative regulator of HCC progression.